PELATIHAN DAN PENDAMPINGAN PENYUSUNAN PERANGKAT PEMBELAJARAN BERBASIS TPACK DI SD - Ratman; Kasmudin Mustapa; Sri Hastuti Virgianti Pulukadang; Nurida (Jurusan Farmasi FMIPA Universitas Tadulako, 2024)
Training and mentoring in the development of TPACK-based learning devices were conducted at SD Inpres 3 Talise. The training participants are 16 elementary school teachers. The training is conducted by administering an initial test, followed by the presentation of training materials. The next step is the mentoring in the preparation of learning devices, where participants are given a final test and a questionnaire to gather their responses to the training and mentoring activities. Data from the pre-test and post-test were processed using the N-gain formula and N-gain interpretation categories. The results of the participant response questionnaire showed that 93.75% of teachers prepared well for the training and mentoring, 93.75% of the training materials were relevant to the teaching profession, and 100% of the participants expressed that the training and mentoring were very beneficial for teachers. The results of the data analysis showed that all participants experienced an improvement in test scores, with 1 person showing an increase of g > 0.70, 3 ≤ g ≤ 0.7 (high category) and 15 other participants with an increase of 0.3 ≤ g ≤ 0.7. (kategori sedang). Based on the interpretation of N-gain effectiveness, with an increase in N-gain value >76, it can be said that the training and mentoring in the preparation of TPACK-based learning devices were effectively carried out by the service team from Tadulako University.